Assessment of the Appropriateness of Compensation for Converted Slope Farmland in Yunnan Province, China - Wang, Zanxin; Calderon, Margaret M.; Carandang, Myrna G. (2008)
The study assessed the appropriateness of compensation rates under the Upland Conversion Program (UCP) from the regional economy and farmer perspectives. The compensation rates were calculated according to the criterion that the compensation payments should at least offset the UCP’s negative impacts on the regional gross output and farmers’ income, respectively. A regional input-output model was developed to measure the economic impacts of the UCP. The results showed that the existing compensation rate was much higher than the calculated rates from both perspectives, and the calculated compensation rate from the regional economy perspective was higher than from the farmers’ perspective. The results of the study have policy implications for improving the cost-effectiveness of the UCP. It is suggested that the compensation be paid in two parts, one for farmers to offset their income loss, and another for developing substitute industries to partially offset the negative impacts of the UCP on the regional economy.
Keywords: Rural land use; Agricultural economics